SISTEM PENGENDALIAN INVENTORY TURNOVER DENGAN PENDEKATAN MAQASHID SYARIAH (Studi pada PT Al Faqih Putra Risjaya di Kabupaten Bone) - Andi Gusriana Fatimah; Munawarah Munawarah (Institut Agama Islam Negeri Bone, 2021)
This research aimns to find out about inventory turnover control system and implementation of Maqashid Sharia in the furniture business at PT Al Faqih Putra Risjaya. As for inventory turnover control system is the process of regulating and monitoring policies in determining the level of inventory that must be maintained by the company, and maqashid sharia means the unity of principles, words and actions based on achieving the pleasure of Allah SWT. The type used in this research is field research, that is research conducted directly by collecting information in the form of data from interviews, observations, and documentation. The results of this research indicate that the inventory turnover control system applied by PT Al Faqih Putra Risjaya is still natural and simple, that is procuring raw material inventories based on company conditions and previous experience. PT Al Faqih Putra Risjaya also applies the safety stock method and also the economic order quantity method, namely purchasing raw materials in large quantities to minimize inventory shortages due to natural conditions such as the rainy season which affects the delay in the distribution of raw materials. In terms of inventory turnover, PT Al Faqih Putra Risjaya is also doing well. This can be seen from the sales results that continue to increase from 2018-2020. And overall, there has been an application of maqashid sharia in the furniture business at PT Al Faqih Putra Risjaya. This can be seen through the fulfillment of 5 aspects of maqashid sharia at PT Al Faqih Putra Risjaya, that are: 1) protecting religion, 2) protecting of soul, 3) protecting the mind, 4) protecting offspring, and 5) protecting the property.